2022
DOI: 10.3390/ijerph19052589
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurial Resilience: A Case Study on University Students

Abstract: Entrepreneurial resilience refers to the capacity to face, overcome and project oneself after suffering life events with a negative impact. Emerging adulthood and the characteristics of university life facilitate the occurrence of stressful situations that can affect well-being. The aim of this phenomenological research is to explore the strategic components of entrepreneurial resilience and how young university students have shaped their entrepreneurial resilience after experiencing negative life events. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 117 publications
0
2
0
Order By: Relevance
“…This indicates that resilience is closely linked to adaptability and flexibility, which are essential for successful venture creation. This finding is in line with the research of Montoro-Fernández, Cárdenas-Gutiérrez, and Bernal-Guerrero (Cárdenas-Gutiérrez et al 2022), which discovered that resilience undergraduate students exhibited greater adaptability and flexibility in response to unexpected challenges. The finding also supports the study of Brewer et al (2019), which revealed that resilience undergraduate students are more likely to embrace learning opportunities, seek feedback and engage in continuous learning and self-improvement.…”
Section: Discussion Of Findingssupporting
confidence: 91%
See 1 more Smart Citation
“…This indicates that resilience is closely linked to adaptability and flexibility, which are essential for successful venture creation. This finding is in line with the research of Montoro-Fernández, Cárdenas-Gutiérrez, and Bernal-Guerrero (Cárdenas-Gutiérrez et al 2022), which discovered that resilience undergraduate students exhibited greater adaptability and flexibility in response to unexpected challenges. The finding also supports the study of Brewer et al (2019), which revealed that resilience undergraduate students are more likely to embrace learning opportunities, seek feedback and engage in continuous learning and self-improvement.…”
Section: Discussion Of Findingssupporting
confidence: 91%
“…Resilient students are also able to set realistic goals and develop a plan of action to achieve them (Fisher et al 2016). They can adapt their plans as circumstances change and are open to feedback and constructive criticism (Cárdenas-Gutiérrez et al 2022). Therefore, students interested in venture creation need to focus on developing their resilience alongside their business and technical skills.…”
Section: Resilience and Venture Creationmentioning
confidence: 99%
“…Scheepers emphasize the importance of an experiential entrepreneurship model in nurturing career management skills and cultivating resilient graduates (Scheepers, 2015). Additionally, Montoro-Fernández delves into the strategic facets of entrepreneurial resilience among university students, identifying both intrapersonal and extrapersonal processes contributing to the development of personal projects (Montoro-Fernández, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The pandemic phenomenon triggers some challenges to be adapted and opportunities to be leverage among the entrepreneurs; a social start up is one of the solution that might assist entrepreneur grows well (Mai et al, 2022). Entrepreneurial resilience is found as a solution for face any challenges and take up any opportunities in phenomenal situation (Montoro-Fernández et al, 2022). This research anticipates that learning process in university is crucial and the best fit learning input providing make a best transition from a student hood to adulthood, for a betterment and sustainable wellbeing.…”
Section: Introductionmentioning
confidence: 99%